Assessment of nitrogen uptake and utilization in drought tolerant and Striga resistant tropical maize varieties - Kamara, A.; Ewansiha, S.U.; Menkir, A. (Informa UK Limited, 2014)
Maize (Zea mays L.) is an important food crop in the Guinea savannas of Nigeria. Despite its high production potential, drought, Striga hermonthica parasitsim, and poor soil fertility particularly nitrogen deficiency limit maize production in the savannas. Breeders at IITA have developed drought- and Striga-tolerant cultivars for testing, dissemination, and deployment in the region. Information on the response of these cultivars to N fertilization is, however, not available. This study evaluated grain yield, total N uptake (TNU), N uptake (NUPE), N utilization (NUTE), and N use efficiency (NUE) of selected maize cultivars along with a widely grown improved maize cultivar at two locations in the Guinea savannas of northern Nigeria. Maize grain yield increased with N application. The average grain yield of the maize cultivars was 76% higher at 30, 156% higher at 60, and 203% higher at 120 kg N ha?1 than at 0 kg N ha?1. This suggests that N is a limiting nutrient in the Nigerian savannas. Five drought-tolerant cultivars produced consistently higher yields when N was added at all levels. These cultivars had either high NUPE or NUTE confirming earlier reports that high N uptake or NUTE improves maize grain yield. The study also confirms earlier reports that maize cultivars that are selected for tolerance to drought are also efficient in uptake and use of N fertilizer. This means that these cultivars can be grown with application of less N fertilizer thereby reducing investment on fertilizers and reduction in environmental pollution.